Anarchism and Moral Philosophy
VIII, 248 p.
Keywords: This collection explores the nature and role of ethics within anarchist thought and practice, examining normative, meta-ethical and applied ethical issues through some of the theoretical insights of anarchism. It comprises contributions from international scholars working within the fields of philosophy and political theory.